2000
DOI: 10.1182/blood.v96.4.1594
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and fibrinolytic activities in 2 siblings with β2-glycoprotein I deficiency

Abstract: β2-Glycoprotein I (β2GPI) is a major antigen for antiphospholipid antibodies, and its multiple in vitro functions have been reported. This glycoprotein not only down-regulates thrombin formation by inhibiting contact activation or prothrombinase activity, but also up-regulates coagulation by reducing protein C anticoagulant activity. However, the in vivo roles of β2GPI remain obscure. Coagulation and fibrinolytic characteristics were investigated in individuals with β2GPI deficiency. An apparently healthy woma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…Bancsi et al (1992) and our team (Yasuda et al, 2000) reported that β2GPI‐deficient families were apparently not at risk of thrombosis. We have also reported that most haemostatic and fibrinolytic markers are normal with any evidence of increased thrombin generation in individuals with congenital β2GPI deficiency (Takeuchi et al, 2000). Moreover, plasma β2GPI levels in patients with APS have been reported to be either normal (de Benedetti et al , 1992) or elevated (Galli et al , 1992; McNally et al , 1995).…”
Section: Discussionmentioning
confidence: 69%
“…Bancsi et al (1992) and our team (Yasuda et al, 2000) reported that β2GPI‐deficient families were apparently not at risk of thrombosis. We have also reported that most haemostatic and fibrinolytic markers are normal with any evidence of increased thrombin generation in individuals with congenital β2GPI deficiency (Takeuchi et al, 2000). Moreover, plasma β2GPI levels in patients with APS have been reported to be either normal (de Benedetti et al , 1992) or elevated (Galli et al , 1992; McNally et al , 1995).…”
Section: Discussionmentioning
confidence: 69%
“…β 2 ‐GPI has been implicated in a variety of physiological pathway, including triglyceride metabolism, blood coagulation, and hemostasis [Takeuchi et al, 2000; Yasuda et al, 2000]. β 2 ‐GPI‐deficient plasma is unable to inhibit the contact activation of blood coagulation [Takeuchi et al, 2000] and this therefore raises the possibility that people deficient in β 2 ‐GPI may be more susceptible to thrombosis. However, the role of β 2 ‐GPI‐deficiency in thrombosis is controversial [Bancsi et al, 1992; Sheng et al, 2001].…”
mentioning
confidence: 99%
“…40 However, individuals with a complete deficiency of β2GPI do not have a clinical phenotype and mice with a null mutation in β2GPI do not display a clear phenotype either. 41,42 β2GPI has an elongated structure and consists of five highly homologous complement-type repeats, or sushi domains, designated as domain (D)I to V. Each domain contains two internal disulfide bonds, with the exception of DV, which contains three and has a slightly aberrant conformation. Both the first and the fifth sushi domains of β2GPI have been reported to interact with phospholipids.…”
Section: β2gpi-dependent Versus β2gpi-independent Lupus Anticoagulantsmentioning
confidence: 99%